The Karoo sand sea in changing climates: Early Jurassic interdune lakes and erg dynamics in southern Africa - Head, Howard Vincent (Department of Geological Sciences, 2023)
Aeolian systems have a particular sensitivity to climate change, and where these are preserved in the geological record, they can provide insights into palaeo-climatic drivers of erg dynamics through time. This thesis investigates the sedimentary geology of the southern extension of a vast ancient desert system that was active over Pangaea and formed part of one of the largest known sand seas in Earth's history. The Lower Jurassic Clarens Formation in the main Karoo Basin of southern Africa has been interpreted as an aeolian succession that is dominated by massive sandstones in the lower and upper parts of the unit, whereas large-scale cross-bedded sandstones are mostly associated with its middle part. Lenticular mudstones and sandstones with ripple marks, ripple crosslamination, horizontal lamination and desiccation cracks have also been reported from the lower and upper parts of the succession. Based on the stratigraphic distribution of the sedimentary facies, the formation is informally subdivided into 3 zones that seem to reflect a wet-dry-wet climate megacycle. To date, the age of the formation is based on a very small detrital zircon dataset, the bioand chronostratigraphy of the conformably underlying Elliot Formation and the radioisotopic dates of Drakensberg Group basalts that are conformably overlying the Clarens Formation. Thus far, few investigations have targeted the evolution of this Early Jurassic fluvio-lacustrine-aeolian system, and the origin of massive sandstone facies that dominates parts of the formation. Therefore, this study re-evaluates the origin and basinal distribution of the sedimentary facies, and the spatiotemporal controls on erg development during the deposition of the Clarens Formation. Moreover, this study provides the first robust chronostratigraphic framework and provenance history for this iconic Early Jurassic aeolian system of southwestern Gondwana. The wet-dry-wet climate megacycle is not only corroborated herein, but using maximum depositional ages from detrital zircons, these climatic changes are now better dated. The results show a Late Sinemurian wet phase, an larly Pliensbachian dry phase and a late Pliensbachian wet phase during Clarens times. Newly documented field evidence shows that ponds and large lakes coexisted with aeolian dunes, with sand sheets, loess plains and fluvial systems having been established downwind. The size of the late Sinemurian ponds and lakes were controlled by their proximity to the erg margin, such that small ponds developed close to the erg centre, and large lakes were established along the erg margin. By the Early Pliensbachian, an intensification of the arid conditions led to the increased availability of sediments for aeolian entrainment, resulting in expansion of the erg eastward. Wet conditions ensued once again in the Late Pliensbachian, and lead to the contraction of the erg and expansion of loess plains with seasonally wet interdunes. Sediment, mostly supplied from the west, was overwhelmingly recycled from pre-existing, Karoo-age deposits and sedimentary rocks associated with the Pan-African orogeny, although evidence for some non-sedimentary and young, syn-Clarens sources are also present. The youngest zircon population show subtle temporal and spatial trends that can be used as proxies for the erg development. The late Sinemurian signal is identified in the lower zone in the south of the basin and is incorporated in subsequent zones in the central and northern parts of the basin, suggesting that, although the main wind direction was from the west northwest, the basin was filled from south to north. This newly established temporal framework of the wet-dry-wet climate cycle in the Clarens Formation corresponds well with the palaeoclimatic trends interpreted for the Tethyan margin of Gondwana, signifying that this may have been a global trend in the Early Jurassic.